INFLUENCE OF INCREASING THE MILK YIELD FOR THE FIRST LACTATION OF THE LITHUANIAN HEAVY DRAFT HORSES ON THEIR PRODUCTIVE LONGEVITY - Chirgin Evgeny Dmitrievich; Semenov Vladimir Grigoryevich; Baimukanov Dastanbek Asylbekovich; Iskhan Kairat Zhalelovich; Rzabayev Tolybek Serikbayevich; Zhikishev Yerlik Kaliaskarovich (Scientific Journal of Pedagogy and Economics, 2019)
Horses are late-ripening animals with low fecundity and therefore should be used in dairy horse breeding for a long time to ensure the profitability of the industry. In Central Russia, mare's milk is produced from draft horse breeds, including Lithuanian heavy-draft horses. They are highly productive animals. With intensive increasing the milk yield for the first lactation, the lifetime milk yield and the period of productive use may be declined. Studies have shown that the optimal level of increased milk yield for Lithuanian draft mares is 3001-4000 kg of milk. At this level, the mares give the highest possible lifetime yield of 24,403.66 and the highest amount of milk fat and milk protein. If the increase in the milk yield for the first lactation reaches 6000 kg and above, then in mares of the studied breed the period of productive use and the lifetime yield reduce.